(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The purpose of this paper is to search for thearchaeological relics which has not been documented before, and are preservedin some or the other manner in the villages of north-west district of Delhi.Primarily the work intends to focus at the present perceptions of the villagerstowards these relics. This is based on the field study of several villageswhich unveiled several historical remnants. The revelation of these remnants,especially the sculptures, is the most significant element in this paper andthus, is examined in detail.